Subdermal Ultrasound Contrast Agent Injection for Sentinel Lymph Node Identification: An Analysis of Safety and Contrast Agent Dose in Healthy Volunteers. (5th December 2017) - Machado, Priscilla; Stanczak, Maria; Liu, Ji‐Bin; Moore, Jason N.; Eisenbrey, John R.; Needleman, Laurence; Kraft, Walter K.; Forsberg, Flemming
Abstract : Objectives: Mapping of the lymphatic chain for identification of the sentinel lymph node (SLN) is an important aspect of predicting outcomes for patients with breast cancer, and it is usually performed as an intraoperative procedure using blue dye and/or radiopharmaceutical agents. Recently, the use of contrast‐enhanced ultrasound (CEUS) has been proposed as an alternative imaging technique for this mapping. The objective of this study was to evaluate the use of subdermal administration of the ultrasound (US) contrast agent Sonazoid (GE Healthcare, Oslo, Norway) in terms of patient safety and to select the dose to be used for lymphatic applications in humans. Methods: This study was performed in 12 female volunteers who received bilateral subdermal injections of Sonazoid (1 or 2 mL dose) in the mid‐upper outer quadrant of their breasts at 2 different time points. Contrast‐enhanced US examinations were performed 0, 0.25, 0.5, 1, 2, 4, 6, and 24 hours after injection to identify SLNs. Results: Sentinel lymph nodes were identified within the first hour after injection as enhanced structures, and there was no significant difference by dose in the number of SLNs identified ( P  = .74). The volunteers only had minor adverse experiences (AEs) that resolved completely without intervention by study completion. Conclusions: The subdermal use of Sonazoid in this study showed only minor local and nonsignificant AEs that were completely resolved without any intervention. Two different doses were compared with no significant differences observed between them. Hence, the lower dose studied (1 mL) was selected for use in future clinical studies.